2019
DOI: 10.1029/2018jb016054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Crustal Rheology on Temperature‐Dependent Viscoelastic Models of Volcano Deformation: Application to Taal Volcano, Philippines

Abstract: We use ALOS-1 interferometric synthetic aperture radar data spanning the period of 2007-2011 to obtain time-dependent ground deformation data over Taal caldera related to the 2010-2011 volcanic unrest, which did not lead to an eruption. We employ finite element models that account for subsurface thermomechanical properties to test for viscoelastic deformation. We also examine the variability of crustal rheological parameters of the temperature-dependent Arrhenius formulation for viscosity, to investigate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 72 publications
(113 reference statements)
0
26
0
Order By: Relevance
“…Other studies apply spatially varying viscosity models, such as Morales Rivera et al. (2019) used for the 2010–2011 Taal volcano unrest and Del Negro et al. (2009) used for the 1993–1997 Etna volcano inflation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies apply spatially varying viscosity models, such as Morales Rivera et al. (2019) used for the 2010–2011 Taal volcano unrest and Del Negro et al. (2009) used for the 1993–1997 Etna volcano inflation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to elevated crustal temperature in volcano roots, viscoelastic relaxation may be pronounced in relation to large‐volume magma transfer events. Multiple studies have focused on viscoelastic deformation related to rifting events and volcanic eruptions, for example, following dyking events during the 2005–2010 Dabbahu rifting episode at Afar (Hamling et al., 2014), at the Kutcharo caldera, Japan (Yamasaki et al., 2018), at Taal volcano (Morales Rivera et al., 2019) and Laguna del Maule volcano in Chile (Novoa et al., 2019). During the 2005–2010 Dabbahu rifting episode, continuous displacements were observed by Interferometric Synthetic Aperture Radar (InSAR) and Global Navigation Satellite System (GNSS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the SLS model, we have demonstrated that the relative weightings of the elastic arm ( μ 0 ) and the Maxwell arm ( μ 1 ) strongly influence both the asymptote magnitude and the timescale of convergence; however, there is little experimental evidence to suggest how these values should be allocated other than on the basis to reduce misfit. As a result, an equal weighting of 0.5 is most common (e.g., Del Negro et al, ; Gottsmann & Odbert, ; Hickey et al, , , ; Le Mével et al, ; Morales Rivera et al, ). However, insight into the weighting of the fractional shear moduli may be gained from the ratio of instantaneous (elastic) to time‐dependent (viscous) deformation (Figure g), and so it may be possible to derive alternative relative contributions from deformation time series, but the use should be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…During the last 40 years, no eruptive activity was recorded; given the past eruption history, an unusual quiescence period was realized by the scientists. Seismological [54,55], geochemical [56], electromagnetic [55,57], thermal [52,58], and InSAR crustal deformation measurement [59] techniques were used to monitor activities of the Taal volcano. Efforts were made to map the 3-D structure and monitor the volcanic activities and observations of geophysical parameters (magnetic, electric, tilt, resistivity, ground and water temperature).…”
Section: Volcano Monitoringmentioning
confidence: 99%